Health, Nutrition and Family Welfare Programme Review of Progress during the Ninth Plan Period - Planning Commission (Planning Commission Government of India, 2001)
The review of Health, Nutrition, and Family Welfare programmes during India’s Ninth Five-Year Plan (1997–2002) provides a comprehensive assessment of achievements, challenges, and strategic recommendations. Despite substantial investments in healthcare infrastructure, inefficiencies persist at the primary care level, leading to inconsistent service delivery and underutilization of resources. The period witnessed positive demographic changes, but high morbidity rates from communicable and non-communicable diseases remain a concern. Key strategies included decentralized, area-specific health planning, integration of services, human resource development, and enhanced infrastructure in underserved regions. Initiatives in Indian Systems of Medicine & Homeopathy (ISM&H) emphasized curriculum reforms, medicinal plant conservation, clinical skill enhancement, and quality control. Family Welfare programmes focused on improving contraceptive access, maternal and child health services, NGO engagement, and Panchayati Raj participation. The Ninth Plan allocated significant funding to support these efforts, aiming to enhance equity, efficiency, and access in healthcare delivery. The review underscores the need for integrated, community-centered approaches, strengthened monitoring, and sustainable financing to achieve long-term improvements in India’s health, nutrition, and population welfare outcomes.
Planning Commission Government of India February 2001
Keywords: Health Programmes; Nutrition; Family Welfare; Ninth Five-Year Plan; Primary Healthcare; ISM&H; Medicinal Plants; Reproductive Health; NGOs; Panchayati Raj Institutions; Population Policy; Healthcare Infrastructure